就 那條 發(fā)視頻的 一視頻 一結(jié)論 之證明 饗以諸君

即
不等式
a/sin^mθ+b/cos^mθ
≥
(a^(2/(m+2))+b^(2/(m+2)))^((m+2)/2)
之證明
設(shè)
sinθ=p
cosθ=q
有
p2+q2=1
即
-amp^(-m-1)
/
p
=
-bmq^(-m-1)
/
q
即
ap^(-m-2)
=
bq^(-m-2)
即
p=(b/a)^(-1/(m+2))q
即
((b/a)^(-2/(m+2))+1)q2=1
即
q
=? ?
a^(-1/(m+2))
/
(a^(-2/(m+2))+b^(-2/(m+2)))^(1/2)
p
=
b^(-1/(m+2))
/
(a^(-2/(m+2))+b^(-2/(m+2)))^(1/2)
有
a/p^m+b/q^m
即
a/sin^mθ+b/cos^mθ
得
最小值
a(a^(-2/(m+2))+b^(-2/(m+2)))^(m/2)
/
b^(-m/(m+2))
+
b(a^(-2/(m+2))+b^(-2/(m+2)))^(m/2)
/
a^(-m/(m+2))
=
(
a^(2/(m+2))
(a^(-2/(m+2))+b^(-2/(m+2)))^(m/2)
+
b^(2/(m+2))
(a^(-2/(m+2))+b^(-2/(m+2)))^(m/2)
)
/
(ab)^(-m/(m+2))
=
(a^(2/(m+2))+b^(2/(m+2)))
(a^(-2/(m+2))+b^(-2/(m+2)))^(m/2)
/
(ab)^(-m/(m+2))
=
(a^(2/(m+2))+b^(2/(m+2)))
(a^(-2/(m+2))+b^(-2/(m+2)))^(m/2)
/
((ab)^(-2/(m+2)))^(m/2)
=
(a^(2/(m+2))+b^(2/(m+2)))
(a^(-2/(m+2))+b^(-2/(m+2)))^(m/2)
((ab)^(2/(m+2)))^(m/2)
=
(a^(2/(m+2))+b^(2/(m+2)))
(b^(2/(m+2))+a^(2/(m+2)))^(m/2)
=
(a^(2/(m+2))+b^(2/(m+2)))^((m+2)/2)
即
a/sin^mθ+b/cos^mθ
≥
(a^(2/(m+2))+b^(2/(m+2)))^((m+2)/2)
得證
ps.
有關(guān)那條
罄竹難書
是那什么
還想立牌坊
骯臟齷齪
腌臜不堪
“秒殺大招”
發(fā)視頻的
無恥行徑
詳見
與
與